Palace Communication and Public Relations in Traditional Governance: A Focus on the Asante Kingdom - Owusu Prempeh, Dorigen (UniMAC - GIJ, 2017)
Traditional goveluance, represented in the chieftaincy institution, relnains very prominent in Ghanaian socio-political life, notwithstanding the modern Western-oriented political governance system that the country practises. As a political systeln, chieftaincy reflects power relations between traditional political authority and inhabitants with the seat of government being the Palace. Like every other institution, cotnmunication plays a crucial role in the administration of the affairs of the traditional society. Yet while much work has been done of the chieftaincy institution, especially in sociology, very little studies exist on how communication works in this setup and the communication dynamics therein. This is why this study, which seeks to investigate the communication roles of the Okyeame in the palace setup is very relevant today. Specifically, the study strives to discover whether the Okyeanle's communication roles share a symbiotic relationship with public relations. The study focuses on the Manhyia palace and is guided by the Systems Theory (Dozier, Grunig and Grunig, 2002). It is supported by a qualitative research methodology that used semistructured interviews and observation to collect data for analysis. The findings revealed that the institution of the okyeame is central to the operations of the Manhyia palace. The okyeame is regarded as the king's wife and has unlitnited access to the king. The okyeame used to play more roles in the past than now. He used to run errands for the king, he was the public relations officer, the human resource manager, pours libation on some occasions and is the king's representative. However, due to the expansion of the Asante kingdoln and the high division of labour of the Manhyia palace under Otulnfuo Osei Tutu II, the Okyeame is now mostly seen to be a representative of the king at celiain gatherings and relays information between the king and his subjects. Major public relations activities are carried out by consulted public relations finns for the Otumfuo.
Thesis